CINR Performance of Downlink Mobile WiMAX IEEE 802.16e Deployed Using Coexistence Cellular Terrestrial and HAPS - I. Iskandar; Andi Wahyudi (LPPM ITB, 2014)
Deploying WiMAX through High Altitude Platform Station (HAPS) system is a new means of wireless delivery method and thus attracting much the attention in a telecommunication society. However delivering WiMAX through the terrestrial network has already been started a few years ago. Therefore, we need to look at the scenario of coexistence system both of HAPS and terrestrial in delivering WiMAX services. This paper evaluates the performance of coexistence system between cellular HAPS and terrestrial for the downlink scenario when they are transmitting WiMAX mobile 802.16e services. Our evaluation is based on the performance simulation of coexistence model using two methods. First method is a footprint exchange between the two systems.The second method is a combination of footprint exchange and HAPS footprint enhancement. The proposed methodsare then evaluated by computer simulation in terms of carrier to interference plus noise ratio (CINR) performance. In general, both methods resulting performance enhancement in CINR quality compared with coexistence deployment with normal scenario of the cell configuration used by HAPS and terrestrial. The method of combining footprint exchange and HAPS footprint enhancement is able to improve CINR more than 10 dB compared with the normal footprint configuration for all users location inside the coverage.